2010
DOI: 10.1002/hyp.7802
|View full text |Cite
|
Sign up to set email alerts
|

Relating hydrogeomorphic properties to stream buffering chemistry in the Neversink River watershed, New York State, USA

Abstract: Abstract:Monitoring the effects of acidic deposition on aquatic ecosystems in the Northeastern US has generally required regular measurements of stream buffering chemistry (i.e. acid-neutralizing capacity (ANC) and calcium Ca 2C ), which can be expensive and time consuming. The goal of this paper was to develop a simple method for predicting baseflow buffering chemistry based on the hydrogeomorphic properties of ten nested watersheds in the Neversink River basin (2Ð0-176Ð0 km 2 ), an acid-sensitive basin in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…We hypothesized that upland tributaries may drain calcium‐poor materials in moderately buffered areas such as the Taconic Range, producing (a) relatively low ANC values; (b) moderate susceptibility to acidification; and (c) temporal patterns of recovery from decreased acid deposition and longitudinal gradients distinct from those recorded by poorly buffered streams. Longitudinal gradients in upland streams are significant because stream chemistry measured at a site is an aggregated property that integrates the chemistry and surface area of rock and organic materials, mean travel time, reaction rates, and the mixing of flow from different upstream source areas (Harman, ; Harpold, Shaw, Burns, Walter, & Steenhuis, ), including precipitation. In this paper, we use long‐term hydrogeochemical data to test how (a) acid deposition affects the chemistry of streams that drain upland forested catchments underlain by moderately to well‐buffered geologic materials; (b) mixing of water from different source areas affects longitudinal and short‐term changes in stream chemistry; and (c) the chemistry of moderately buffered streams has recovered in response to decreased acid deposition during the past two decades.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that upland tributaries may drain calcium‐poor materials in moderately buffered areas such as the Taconic Range, producing (a) relatively low ANC values; (b) moderate susceptibility to acidification; and (c) temporal patterns of recovery from decreased acid deposition and longitudinal gradients distinct from those recorded by poorly buffered streams. Longitudinal gradients in upland streams are significant because stream chemistry measured at a site is an aggregated property that integrates the chemistry and surface area of rock and organic materials, mean travel time, reaction rates, and the mixing of flow from different upstream source areas (Harman, ; Harpold, Shaw, Burns, Walter, & Steenhuis, ), including precipitation. In this paper, we use long‐term hydrogeochemical data to test how (a) acid deposition affects the chemistry of streams that drain upland forested catchments underlain by moderately to well‐buffered geologic materials; (b) mixing of water from different source areas affects longitudinal and short‐term changes in stream chemistry; and (c) the chemistry of moderately buffered streams has recovered in response to decreased acid deposition during the past two decades.…”
Section: Introductionmentioning
confidence: 99%
“…These natural sources of metals, along with the anthropogenic enrichment from mining operations (Alsina et al, ; Bugueno, Acevedo, Bonilla, Pizarro, & Pasten, ; Leiva et al, ; Oyarzun & Oyarzun, ; Oyarzun et al, ) affect both water and sediment quality within the region. It is well known that the origin and effects of acid mine drainage and acid rock drainage are largely controlled by hydrological processes (Cravotta, Goode, Bartles, Risser, & Galeone, ; Harpold, Burns, Walter, Shaw, & Steenhuis, ; Johnson & Thornton, ; Kimball, Broshears, Bencala, & McKnight, ; McKnight et al, ; Papassiopi et al, ; Pellegrini, Garcia, Penas‐Castejon, Vignozzi, & Costantini, ; Wan, Liu, Munroe, & Cai, ). A systematic increase in the concentration of arsenic, copper, iron, and sulfate in Andean watersheds (Pizarro, Vergara, Rodriguez, & Valenzuela, ; Pizarro, Vergara, Morales, Rodriguez, & Vila, ) highlights the need to further improve conceptual models and expand datasets describing the processes underlying the behavior of dissolved and particle‐bound metal fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in the Neversink have demonstrated that stream ANC values are strongly correlated to aquatic biota communities, including the species richness of macroinvertebrates (Ernst et al 2008), diatoms (Burns et al 2008), mussels (Baldigo et al 2002(Baldigo et al , 2003, and fish , Van Sickle et al 1996, Baldigo and Lawrence 2000. Interestingly, ANC values are highly variable across the Neversink River watershed, requiring dense, and presumably expensive, biotic monitoring to effectively assess potential ecological recovery (Harpold et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous explanations for the differences in baseflow ANC values of sub-watersheds within the Neversink basin have been offered, including geological heterogeneities as reflected by the underlying bedrock lithology Murdoch 1991, Baldigo andLawrence 2000), the distribution of groundwater springs (Burns et al 1998, Baldigo and Lawrence 2000, Shaman et al 2004, watershed area or topography (Wolock et al 1997, Vitvar et al 2002, Shaman et al 2004, and elevation gradients in acidic deposition ). More recently, Harpold et al (2010) showed that variability in baseflow ANC (À20 to 128 leq/L) in the Neversink can largely be explained by differences in watershedscale hydrology, which is driven by differences in watershed slope and drainage density. Harpold et al (2010Harpold et al ( ) used 1991Harpold et al ( -1993 stream chemistry and hydrologic data, which corresponded to a period when the acidity of atmospheric deposition was greater than at present (Murdoch and Shanley 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation